Effect of Annealing Temperature on the Structure, optical and Electronic Properties of \(\text{TiO}_{2}\) Made by Thermal Treatment of \(\text{Ti}\) - Chien, Dang Tran; Long, Pham Duy (Communications in Physics, 2014)
In this work, TiO\(_{2}\) nanocrystalline thin films were obtained through evaporating Ti films by Electron Beam Deposition (EBD) followed by thermal treatment. The deposition speed of Ti thin fims was carried out at 0.15 nm/s and 1 nm/s. The results show that after annealing at 450\(^°\)C for 8 h, the obtained TiO\(_{2}\) thin films have nanoparticle structure with grain size of 20 nm for the Ti thin film deposited at the rate of 1nm/s, whereas at the a deposition rate of 0.15 nm/s, the TiO\(_{2}\) has a nanorod structure with the rod length of 300 -- 400 nm. At 700\(^°\)C for 8 h, the rutile phase was formed. At annealing temperature of 450\(^°\)C, all the samples are close to the stress free TiO\(_{2}\). The band gap of TiO\(_{2}\) thin films decreased with annealing temperature in both doposition rate of Ti thin films. The response of the films annealed at 450\(^°\)C presented a faster rise and fall in photocurrent under UV illumination on and off interval. Nanoporous structure TiO\(_{2}\) shows photoelectronic property better than that of nanorod structure. The obtained TiO\(_{2}\) films were characterized by X-ray diffraction (XRD) and a field emission scanning electron microscope (FE-SEM). The TiO\(_{2}\) films were used in a photo-electrochemical (PEC) cell as a working electrode and a platinum electrode as a counter electrode. The electrolyte solution contains 1 M KCl and 0.1 M Na\(_{2}\)S.